South Asia Economic Focus, Fall 2015 : Getting Prices Right--The Recent Disinflation and Its Implications - World Bank (Washington, DC, 2015)
The South Asia Economic Focus is a biannual economic update presenting recent economic developments and a near term economic outlook for South Asia. It includes a Focus section presenting more in depth analysis of an economic topic of relevance for stability, growth and prosperity in the region as well as country briefs covering Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka. It concludes with a data section providing key economic indicators for South Asia "at a glance". Overall, it aims at providing important background information and timely analysis of key indicators and economic and financial developments of relevance to World Bank Group operations and interaction with counterparts in the region, particularly during annual and spring meeting